Gender and story in South India - Prasad, Leela; Bottigheimer, Ruth B.; Handoo, Lalita (SUNY series in Hindu studies., 2006)
Gender and Story in South India presents exciting ethnographic research by Indian women scholars on Hindu and Muslim women-centered oral narratives. The book is unique for its geographic and linguistic focus on South India, for its inclusion of urban and rural locales of narration, and for its exploration of shared Hindu and Muslim female space. Drawing on the worldviews of South Indian female narrators in both everyday and performative settings, the contributors lead readers away from customary and comfortable assumptions about gender distinctions in India to experience a more dialogical, poetically ordered moral universe that is sensitive to women's material and spiritual lives. Book jacket.